Hydrochemical investigations on waste disposal areas of industrial activities at Rio Claro, São Paulo, Brazil - Bonotto, D. M. [UNESP]; Oliveira, E. G. [UNESP] (My University, 2001)
Groundwaters and surface waters around two waste disposal areas at Rio Claro municipality, nearly in the center of São Paulo State, Brazil, were chemically analysed with the purpose of evaluating the influence on the water quality of the chemicals released without any care with the environment and using a prevention system for the containment of environmentally polluting substances.